Adubos verdes, planta de cobertura, calagem e gessagem como forma de recuperação de um Latossolo Vermelho degradado - Rosa, Poliana A.L. [UNESP]; Alves, Marlene C. [UNESP]; de Souza, Epitácio J. [UNESP]; Bonini, Carolina dos S.B. [UNESP]; Videira, Ligia M.L. [UNESP] (My University, 2017)
The objective of this study was to evaluate the degree of recovery of a cerrado soil, after 21 years of interventions for its recovery. The experimental design was a randomized complete block design with four replications. The treatments were 3 legumes as green manures (for 7 years) associated to the application of limestone and gypsum, and 14 years with a grass as cover crop in total area. The treatments for soil recovery were efficient and reaching up to the 0.20 m soil layer.
Green manures, cover crops, lime and gypsum as a means of recovery of degraded soil
Keywords: Human interference; Organic material; Soil degradation; Urochloa decumbens